Experimental Investigations on the Chemo-Mechanical Coupling in Solid-State Batteries and Electrode Materials - Jiaxuan Wang; Feng Hao (Energies, 2023)
Increasing attention has been paid to the safety and efficiency of batteries due to the rapid development and widespread use of electric vehicles. Solid-state batteries have the advantages of good safety, high energy density, and strong cycle performance, and are recognized as the next generation of power batteries. However, solid-state batteries generate large stress changes due to the volume change of electrode materials during cycling, resulting in pulverization and exfoliation of active materials, fracture of solid-electrolyte interface films, and development of internal cracks in solid electrolytes. As a consequence, the cycle performance of the battery is degraded, or even a short circuit can occur. Therefore, it is important to study the stress changes of solid-state batteries or electrode materials during cycling. This review presents a current overview of chemo-mechanical characterization techniques applied to solid-state batteries and experimental setups. Moreover, some methods to improve the mechanical properties by changing the composition or structure of the electrode materials are also summarized. This review aims to highlight the impact of the stress generated inside solid-state batteries and summarizes a part of the research methods used to study the stress of solid-state batteries, which help improve the design level of solid-state batteries, thereby improving battery performance and safety.